Effects of Sodum Bicarbonate supplementation on Renal function and Nutritional status in Chronic Kidney Disease patients - Saha, Swapen Kumar; Ghosh, Liton Chandra; Akhter, Mahbuba; Sarker, Nayan Ranjan; Khan, N A (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Metabolic acidosis is commonly associated with chronic kidney disease which causes progressive loss of kidney function. The diminishing ability of the kidneys to maintain acid-hase homeostasis results in acid accumulation, leading to various complications such as impairment in nutritional status, worsened uremic bone disease and an association with increased mortality. Recent clinical trials have suggested that correction or prevention of metabolic acidosis by alkali administration is able to attenuate kidney damage and to slow progression of chronic kidney disease and improve nutritional status. Methods: It was a prospective study. Out of a total of 66 CKD patients (eGFR<60 ml/1min/1.73m2 serum HCO,- 16-22 mmol/l); 33 were in treatment group and 33 in control group were included in the study. Treatment group of the study was CKD patients who received sodium bicarbonate for 6 months to correct acidosis. Control group for the study was CKD patients who did not receive any NaHCO, supplementation; attending SSMC, Mitford Hospital for the same duration. Baseline renal function and nutritional status parameters were similar in both groups. Rate of progression of CKD was measured by calculation of eGFR (4 variable MDRD- equation) at the beginning of the study and then after 3 and 6 months. Similar dietary advice was given to both groups. Purposive sampling was done. The primary end point was denoted as rate of eGFR decline. Secondary end points were serum albumin (<35gm/dl) and mid-arm circumference (<24 cm) and body mass index. Nutritional status was determined by measuring mid-arm circumference, serum albumin and body mass index at the starting of the study, after 3 and 6 months. Results: Mean age (years) was 56 ± 15 & 49 ± 15;p-0.074 in treatment and control group respectively. Mean haemoglobin concentration (gm/dl) was 9.8 ± 1.5 and 9.6 ± 0.9;p=0.477 in treatment & control group respectively. At baseline mean BMI (kg/m3) was 21.3±5 and 23±4;p=0.138 in control and treatment group respectively. In the present study, mean systolic blood pressure was 129.6±3.8 and 131.4±5.1;p=0.184 in control and treatment group respectively at six months of study period. In the present study, mean diastolic blood pressure was 79.1±4.6 and 80.8±3.2; p=0.202 in control and treatment group respectively at six months of study period. Serum bicarbonate was raised significantly in treatment group than control group at six months of study period (26.3 ± 1.6 and 21.2± 1.1; p<0.001). Serum potassium was reduced significantly in treatment group than control group at six months of study period (4.5 ± 0.6 and 5±0.5; p=0.001). Mid-arm circumference was increased significantly in treatment group than control group at six months of study period (24.4 and 22.4 cm; p<0.001). Serum albumin (gm/dl) was increased significantly in treatment group than control group at six months of study period (3.4 and 2.8;p<0.001). Body mass index was similar in treatment group and control group at six months of study period (23.1 and 21.2; p=0.090). After six months eGFR (ml/min/m3) was declined significantly in control group than treatment group (3.02± 2.25 and 1.13± 2.31; p=0.001). Conclusion: Oral sodium bicarbonate supplementation in patients with metabolic acidosis slows the rate of decline of renal function in patients with advanced stages of CKD. This easily affordable and simple strategy also improved the nutritional status of advanced stages of CKD patients with metabolic acidosis. J. Dhaka National Med. Coll. Hos. 2017; 23 (02): 08-15